On the Stability of Isolated Iridium Sites in N‐Rich Frameworks Against Agglomeration Under Reducing Conditions. Issue 9 (14th April 2022) - Iemhoff, Andree; Vennewald, Maurice; Artz, Jens; Mebrahtu, Chalachew; Meledin, Alexander; Weirich, Thomas E.; Hartmann, Heinrich; Besmehn, Astrid; Aramini, Matteo; Venturini, Federica; Mosselmans, Fred W.; Held, Georg; et al.
Abstract: Stabilization of single metal atoms is a persistent challenge in heterogeneous catalysis. Especially supported late transitions metals are prone to undergo agglomeration to nanoparticles under reducing conditions. In this study, nitrogen‐rich covalent triazine frameworks (CTFs) are used to immobilize iridium complexes. Upon reduction at 400 °C, immobilized Ir(acac)(COD) on CTF does not form nanoparticles but transforms into a highly active Ir single atom catalyst. The resulting catalyst systems outperforms both the immobilized complex and supported nanoparticles in the dehydrogenation of formic acid as probe reaction. This superior performance could be traced back to decisive changes of the coordination geometry positively influencing activity, selectivity and stability. Spectroscopic analysis reveals an increase of electron density on the cationic iridium site by donation from the CTF macroligand after removal of the organic ligand sphere from the Ir(acac)(COD) precursor complex upon reductive treatment. This work demonstrates the ability of nitrogen moieties to stabilize molecular metal species against agglomeration and opens avenues for catalysts design using isolated sites in high‐temperature applications under reducing atmosphere. Abstract : Formic acid dehydrogenation : Upon reduction at 400 °C, immobilized Ir(acac)(COD) on CTF transforms into a highly active Ir single atom catalyst. The resulting catalyst systems outperforms both the immobilized complex and supported nanoparticles in the dehydrogenation of formic acid as model reaction. This superior performance could be traced back to decisive changes of the coordination geometry and increased electron transfer from the CTF macro‐ligand to the iridium metal site.